Application of Assemblr Edu Media Based on Augmented Reality to Increase The Learning Motivation of Class VIII Students of SMP Negeri 3 Watampone - Syarifnur, Syarifnur; Ihsan B, Ahmad Amalia; Pratiwi, Nesti (International Journal of Education, Information Technology, and Others, 2024)
Application of augmented reality-based assembler edu media to increase learning motivation of students at VIII I SMP Negeri 3 Watampone. Thesis Department of Educational Technology. Faculty of Teacher Training and Education. Muhammadiyah Bone University (supervised by Syarifnur, S.Pd., M.Pd and Ahmad Nurul Ihsan B, S.Pd.I., M.Pd). To develop education in schools, it is necessary to develop presentation media so that students' interest and motivation can increase so that learning outcomes can be understood. Every increasingly sophisticated technological development must be utilized to improve student learning outcomes in ordinary classes. Technology media is used to increase students' interest in learning. learning at school. This research aims to find out how to apply augmented reality-based educational assembly media to increase the learning motivation of students at VIII I SMP Negeri 3 Watampone. The respondents used in this research were 31 students consisting of 16 male respondents and 14 female respondents. Data analysis techniques use the help of Excel and SPSS applications. The research results showed that students' learning motivation in the initial condition was in the low category, namely none, in the good category there were 18 students or 64%, in the very good category there were 12 students or 36%. The questionnaire results reached 55% in cycle I while cycle II only reached 57 which had experienced an increase but only 2% was not included in the maximum category. So the overall results obtained were that there was no direct increase in learning motivation from the application of media to students' learning motivation.